SoundMind Trial: a study protocol for a randomised controlled trial for online acceptance and commitment therapy and sound therapy for tinnitus - Huawei Li; Shan Sun; Xiaoling Huang; Dongmei Tang (BMJ Open)
Introduction Tinnitus is a common ailment that affects 10%–15% of adults worldwide. Comorbidities associated with tinnitus often include hearing loss, emotional distress and sleep disorders, with insomnia being a common issue among patients with tinnitus. Audiological and psychological approaches are typically used to treat chronic subjective tinnitus, with the combination of sound therapy and cognitive–behavioural therapy-based counselling having the strongest evidence for effectiveness. Acceptance and commitment therapy (ACT) has also shown promising effects in reducing the impact of tinnitus when delivered in groups or online. However, there is a lack of evidence on the effects of combining ACT with sound therapy for patients with tinnitus-related insomnia. Therefore, this study aims to compare the efficacy of internet-delivered ACT combined with sound therapy versus sound therapy alone for tinnitus in a superiority, two-arm randomised controlled trial.Methods and analysis A total of 164 patients with chronic subjective tinnitus and insomnia will be randomised to receive internet-delivered guided self-help tinnitus treatment based on ACT combined with tailored sound therapy or tailored sound therapy alone. The primary outcome is the variation in Tinnitus Handicap Inventory scores observed 2 months after randomisation between the two study groups. Secondary outcomes will include insomnia severity, sleep parameters, tinnitus loudness, tinnitus acceptance, depression and anxiety. The outcomes will be assessed at 2, 3 and 6 months post randomisation.Ethics and dissemination The study is approved by the review board and ethics committee of the Eye and ENT Hospital of Fudan University (approval number: 2023066-1). The findings will be disseminated through presentations at relevant conferences and peer-reviewed publications.Trial registration number NCT05963542.